[Tf2n]-Based Ionic Liquids for the Selective Liquid-Liquid Extraction of Levulinic Acid/Formic Acid: Cosmo-Rs Screening and Ternary Lle Experimental Data - Salazar-Gonzalez, R; Romero-Figueroa, J; Quijada-Maldonado, E; Araya-Lopez, C; Olea-Chandia, F; Villarroel-Utreras, E (ELSEVIER, 2022)
The separation of Levulinic (LA) acid and Formic acid (FA) from aqueous streams represents an important and challenging separation in biorefineries, where ionic liquids (ILs) provide a sustainable environment for liquid-liquid extractions of these acids. In this work, a COSMO-RS screening of bis (trifluoromethylsulfonil)imide [Tf2N] (-) based IL was first conducted and then followed by experimental validation to search for the most suitable cation for this separation. After the screening, ternary liquid-liquid equilibrium experiments at 298.15K and the subsequent data correlation using the Non-Random Two Liquid model (NRTL) were performed for future industrial implementation. Results indicated that the phosphonium cations, especially the trihexylthetradecyl phosphonium cation [P66614](+), produced the highest selectivity rates among all the experimentally measured ILs.